Напрямки підвищення якості послуг логістичного консалтингу - Мельничук, Ілля Олексійович; Melnychuk, Illia Oleksiiovych (Національний університет "Львівська політехніка", 2024)
Мельничук І. О., Гречин Б.Д. (керівник). Напрямки підвищення якості послуг логістичного консалтингу. Бакалаврська кваліфікаційна робота – Національний університет «Львівська політехніка». Львів, 2025. Розширена анотація. Ефективність консалтингових послуг залежить від низки об’єктивних та суб’єктивних факторів. Усвідомлення потреби в консалтингу та фаховість самих консультантів ключові чинники в процесі взаємодії на ринку консалтингу [1]. Традиційно аналіз ролі консультування в економіці кожної країни проводять через визначення рівня залученості консультантів до розв’язання управлінських проблем компаній -замовників. Аналізуючи рівень розвитку консалтингової сфери користуються показниками: темп зростання ринку консалтингових послуг та частка консалтингового сектору економіки у ВВП країни [2]. Сучасні світові реалії такі як: війни, локдауни, економічна, політична, фінансова, екологічна та соціальна кризи змушують бізнес коригувати власну діяльність, що пов'язано з управлінням ресурсним забезпеченням [3]. В умовах, які спричинила війна та її наслідки зумовлює бізнес до пошуку альтернатив, тому очевидно, що розвиток сегменту консалтингових послуг може стати одним з каталізаторів відбудови України. Активізація процесів залучення зовнішніх консультантів, зумовлена необхідністю відновлення бізнес-активностей, прискореної інтеграції українських бізнес структур до світового економічного простору та залучення прямих іноземних інвестицій [4]. Логістичний ринок як один із ключових в національній економіці також потребує трансформації логістичних бізнес процесів та скорочення витрат на логістику. Узагальнюючи дослідження специфіки логістичного консалтингу, слід зазначити, що це послуги, які включають інтелектуальні знання та 5 впровадження інновацій, оскільки виявити логістичні проблеми можливо через аудит, а запропонувати вирішення проблеми можливо, користуючись знаннями, навичками, досвідом та застосовуючи інноваційні технології, які істотно поліпшують якість логістичних бізнес-процесів [5]. Об’єктом дослідження в бакалаврській кваліфікаційній роботі є ФОП «Мазурок І.Ю. засновано в 2016 році з основним видом діяльності 63.99 Надання інших інформаційних послуг, н.в.і.у.в. Компанія працює у сфері надання спеціалізованих інформаційних послуг та консалтингу. Станом на 2024 рік компанія функціонує у сфері консалтингу, а саме підбору та навчання персоналу для американської логістичної компанії «Millhouse». Діяльність логістичної компанії «Millhouse» пов’язана з наданням клієнтам повного комплексу послуг з наземного, повітряного, морського транспортування та послуги складської логістики. Наземне транспортування – це експрес-перевезення, перевезення повних вантажів (FTL), негабаритні перевезення, збірних вантажів (LTL). Компанія «Millhouse» підтримує тісні взаємозв’язки із клієнтами, в цілодобовому режимі, щоб забезпечити доставку не тільки вантажів, але й запропонувати клієнту унікальні бізнес-рішення в логістиці. Предметом дослідження в бакалаврській кваліфікаційній роботі є тенденції ринку консалтингу та діяльності ФОП «Мазурок І.Ю. в структурі логістичної компанії «Millhouse». Метою бакалаврської кваліфікаційної роботи є дослідження теоретичних засад логістичного консалтингу та вивчення напрямків підвищення якості послуг логістичного консалтингу. Результати досліджень у бакалаврській кваліфікаційній роботі полягає у розробці рекомендацій щодо покращення якості послуг логістичного консалтингу через впровадження HRM-платформи, що підвищить ефективність системи управління логістичним персоналом. Доцільність впровадження HRM-платформи доведено з економічної точки, розрахувавши коефіцієнт економічної ефективності та термін окупності, а також визначено 6 ряд інших переваг, зокрема: безпеки, гнучкості, індивідуального підходу та підвищення конкурентоспроможності логістичного бізнесу.

Melnychuk I. O., Grechyn B. D. (supervisor). Directions for improving the quality of logistics consulting services. Bachelor's thesis - National University "Lviv Polytechnic". Lviv, 2025. Extended abstract. The effectiveness of consulting services depends on a number of objective and subjective factors. Awareness of the need for consulting and the expertise of consultants themselves are key factors in the process of interaction in the consulting market [1]. Traditionally, the analysis of the role of consulting in the economy of each country is carried out by determining the level of involvement of consultants in solving management problems of customer companies. When analyzing the level of development of the consulting sector, indicators are used: the growth rate of the consulting services market and the share of the consulting sector of the economy in the country's GDP [2]. Modern world realities such as: wars, lockdowns, economic, political, financial, environmental and social crises force businesses to adjust their own activities, which is associated with resource management [3]. In the conditions caused by the war and its consequences, businesses are forced to search for alternatives, so it is obvious that the development of the consulting services segment can become one of the catalysts for the reconstruction of Ukraine. The activation of the processes of attracting external consultants is due to the need to restore business activities, accelerate the integration of Ukrainian business structures into the global economic space and attract foreign direct investment [4]. The logistics market, as one of the key ones in the national economy, also requires the transformation of logistics business processes and the reduction of logistics costs. Summarizing the study of the specifics of logistics consulting, it should be noted that these are services that include intellectual knowledge and the implementation of innovations, since it is possible to identify logistics problems 8 through an audit, and to propose a solution to the problem is possible using knowledge, skills, experience and applying innovative technologies that significantly improve the quality of logistics business processes [5]. The object of research in the bachelor's qualification work is the FOP "Mazurok I.Yu. founded in 2016 with the main activity 63.99 Provision of other information services, n.e.c. The company operates in the field of providing specialized information services and consulting. As of 2024, the company operates in the field of consulting, namely the selection and training of personnel for the American logistics company Millhouse. The activities of the logistics company Millhouse are related to providing clients with a full range of services in land, air, sea transportation and warehouse logistics services. Land transportation is express transportation, full load (FTL) transportation, oversized transportation, consolidated cargo (LTL). The company Millhouse maintains close relationships with clients, around the clock, to ensure the delivery of not only cargo, but also to offer the client unique business solutions in logistics. The subject of research in the bachelor's qualification work is the trends in the consulting market and the activities of the sole proprietorship Mazurok I.Yu. in the structure of the logistics company Millhouse. The purpose of the bachelor's qualification work is to study the theoretical foundations of logistics consulting and study areas for improving the quality of logistics consulting services. The results of the research in the bachelor's qualification work are to develop recommendations for improving the quality of logistics consulting services through the implementation of an HRM platform, which will increase the efficiency of the logistics personnel management system. The feasibility of implementing the HRM platform has been proven from an economic point of view, having calculated the economic efficiency coefficient and the payback period, and a number of other advantages have been identified, in particular: security, flexibility, an individual approach and increasing the competitiveness of the logistics business. 9
Directions for improving the quality of logistics consulting services
Keywords: 6.073.00.00; якість консалтингових послуг; логістичний консалтинг; управління бізнес-процесами; ефективність логістичного персоналу; інноваційні технології; quality of consulting services; logistics consulting; business process management; logistics personnel efficiency; innovative technologies. List of used literature sources. 1. Levishchenko O. Methodological approach to assessing the effectiveness of consulting / Ukrainian Scientific Notes. 2020 No. 6 (78). DOI 10.37491/UNZ.78.2 2. Mazur; N.; & Nikolashin; A. (2021). Consulting services market of Ukraine and the world in the conditions of change / Economy and society; (24). URL: https://doi.org/10.32782/2524-0072/2021-24-15 3. Soroka O. V.; Salo Ya. V. Human resources management using logistic approaches / Economy and society. Issue No. 48 / 2023. DOI: https://doi.org/10.32782/2524-0072/2023-48-22 4. Filiuk G.; Prytula I. Development of the consulting services market in Ukraine in the conditions of modern challenges. Economic analysis. 2024. Volume 34. No. 1. P. 115-125. DOI: https://doi.org/10.35774/econa2024.01.115 5. Nakonechna T.V.; Prokopenko K. O.; Semenova A. K. Logistics consulting as a tool for increasing the efficiency of business processes / Scientific notes of the V. I. Vernadsky Tavrichesky National University. Series: Economics and Management. - 2020. - Vol. 31 (70); No. 6. - P. 124-131